The Challenge of Public Capabilities for Successful Productive Development Policies: Hopeless Task or Pragmatic Program? - Jorge Cornick; Eduardo Fernández-Arias; Ernesto Stein (Inter-American Development Bank (IDB), 2016)
This paper discusses the organizational structure and technical, operational and political capabilities required for successful productive development policies (PDPs). It also discusses how countries can match their PDPs to existing capabilities, as well as expand their capabilities in the long run. The specific difficulties associated with PDPs are also discussed.
hdl:11319/7566
Keywords: H10; H11; L50; O25; 330; Government performance; Industrial policy